# Solve for k 4/3k+2/5=-1-3/2k 43k+25=-1-32k
Combine 43 and k.
4k3+25=-1-32k
Simplify each term.
Combine k and 32.
4k3+25=-1-k⋅32
Move 3 to the left of k.
4k3+25=-1-3k2
4k3+25=-1-3k2
Move all terms containing k to the left side of the equation.
Add 3k2 to both sides of the equation.
4k3+25+3k2=-1
To write 4k3 as a fraction with a common denominator, multiply by 22.
4k3⋅22+3k2+25=-1
To write 3k2 as a fraction with a common denominator, multiply by 33.
4k3⋅22+3k2⋅33+25=-1
Write each expression with a common denominator of 6, by multiplying each by an appropriate factor of 1.
Multiply 4k3 and 22.
4k⋅23⋅2+3k2⋅33+25=-1
Multiply 3 by 2.
4k⋅26+3k2⋅33+25=-1
Multiply 3k2 and 33.
4k⋅26+3k⋅32⋅3+25=-1
Multiply 2 by 3.
4k⋅26+3k⋅36+25=-1
4k⋅26+3k⋅36+25=-1
Combine the numerators over the common denominator.
4k⋅2+3k⋅36+25=-1
Simplify each term.
Simplify the numerator.
Factor k out of 4k⋅2+3k⋅3.
Factor k out of 4k⋅2.
k(4⋅2)+3k⋅36+25=-1
Factor k out of 3k⋅3.
k(4⋅2)+k(3⋅3)6+25=-1
Factor k out of k(4⋅2)+k(3⋅3).
k(4⋅2+3⋅3)6+25=-1
k(4⋅2+3⋅3)6+25=-1
Multiply 4 by 2.
k(8+3⋅3)6+25=-1
Multiply 3 by 3.
k(8+9)6+25=-1
Add 8 and 9.
k⋅176+25=-1
k⋅176+25=-1
Move 17 to the left of k.
17k6+25=-1
17k6+25=-1
17k6+25=-1
Move all terms not containing k to the right side of the equation.
Subtract 25 from both sides of the equation.
17k6=-1-25
To write -1 as a fraction with a common denominator, multiply by 55.
17k6=-1⋅55-25
Combine -1 and 55.
17k6=-1⋅55-25
Combine the numerators over the common denominator.
17k6=-1⋅5-25
Simplify the numerator.
Multiply -1 by 5.
17k6=-5-25
Subtract 2 from -5.
17k6=-75
17k6=-75
Move the negative in front of the fraction.
17k6=-75
17k6=-75
Multiply both sides of the equation by 617.
617⋅17k6=617⋅(-75)
Simplify both sides of the equation.
Simplify 617⋅17k6.
Cancel the common factor of 6.
Cancel the common factor.
617⋅17k6=617⋅(-75)
Rewrite the expression.
117⋅(17k)=617⋅(-75)
117⋅(17k)=617⋅(-75)
Cancel the common factor of 17.
Factor 17 out of 17k.
117⋅(17(k))=617⋅(-75)
Cancel the common factor.
117⋅(17k)=617⋅(-75)
Rewrite the expression.
k=617⋅(-75)
k=617⋅(-75)
k=617⋅(-75)
Multiply 617(-75).
Multiply 617 and 75.
k=-6⋅717⋅5
Multiply 6 by 7.
k=-4217⋅5
Multiply 17 by 5.
k=-4285
k=-4285
k=-4285
The result can be shown in multiple forms.
Exact Form:
k=-4285
Decimal Form:
k=-0.49411764…
Solve for k 4/3k+2/5=-1-3/2k

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top